IN VITRO MUCOLYTIC ACTIVITY DETERMINATION OF N-ACETYL CYSTEINE EFFERVESCENT TABLET USING SUSPENDED LEVEL VISCOMETER - SATISH, NANGUDE; KAMBLE, RAVINDRA; KAJAL, VANHERE (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of the present study was to determine the in vitro mucolytic activity of N-Acetyl Cysteine (NAC) effervescent tablet using egg white solution and suspended level viscometer. Methods: Egg white has similar physicochemical characteristics with airway mucus, thus in vitro mucolytic activity of NAC effervescent tablets was assessed using an egg white solution and a suspended level viscometer. This was also compared with API and marketed effervescent tablets. Outcomes were statistically analysed using a single-factor ANOVA and a paired t-test. Results: The results show, in all three cases, i.e., API, Test tablet, and Commercial tablet, viscosity reduced linearly as the concentration was raised from 10 to 60 mg/10 ml having R2 values 0.9973, 0.9909, 0.9953 respectively. When compared to the negative control solution, viscosity rapidly decreased, which amounted to 71.10 %, 73.03 % and 84.63 % of API, Test tablet and Commercial tablet, respectively. The p values of single factor ANOVA and paired t-test were found to be very less than 0.05 in all cases. Conclusion: NAC effervescent tablet's in vitro mucolytic activity was successfully assessed; results suggested that linearly decreases in viscosity as the concentration of NAC increases and statistical analysis shows significant differences in values.